APLIKASI COUPLER UNTUK MENGATASI GANGGUAN TRAFICK DATA ANTARA STO PONTIANAK CENTRUM – STO SIANTAN PT. TELKOM PONTIANAK - ., Herdi Wiryanto (Jurnal Teknik Elektro Universitas Tanjungpura, 2016)
Transmission system fiber optics between STO Pontianak Centum STO Siantan, now already using two lane fiber optics. The first lane be name"Main" and the second lane "protection", if  the one of lane impaired breaking cable, than be use coupler application for resolve corruption data traffic between STO Pontianak Centrum - STO siantan. For this application usage coupler that has been measured and calculated total attenuation and acceptance on both of  lane, before coupler being installed and after coupler installed. For the result to measurement total attenuation befor intalled coupler on lane "Main" : 9 dB and lane "Protection" :8.5 dB and the result calculation on lane "Main":7.4 db and lane"Protection":10.75 dB. While the results measurement acceptance after installed coupler on lane"protection": -12.5 dBm, and result calculation on lane "Main":-13.4 dBm and lane" Protection": -11.75 dBm. On measurement and calculation total attenuation also acceptance, before and after install coupler, there is a difference result that have find from measurement and calculation. This is because of the difference connectors are not clean, connection that is not "pres" and bending on optical fiber. This difference will not becoming a problem because result that be obtained equally-equally good, and in the circumscription that be given devices (lath). For device attenuation total that is 6 dB until 24 dB, and to receptivity that is -6 dBm until – 24 dBm. After in do it measurement and calculation attenuation total and receptivity before mounted coupler and after mounted coupler, then it can be concluded that the coupler can be used to overcome the interference broken off  the fiber optic cable and a coupler in installed at night and a coupler installation does not require a long time. Keywords: Optical fiber coupler, Application coupler to overcome the interference break up the fiber optic cable, Optical fiber attenuation, Optical fiber transmission systems, Coupler 1 port to 2 port.